Organizational learning in context of part-time employment: A case study of an Estonian media company. Issue 4 (5th September 2016) - Kivipõld, Kurmet; Hoffman, Richard C.
Abstract : Purpose: Combining trends in employment flexibility, organizational learning, need for improved leadership and entrepreneurship is important in managing today's organizations. This study aims to explore these relationships within a single media firm in one of the Baltic States. Design/methodology/approach: The subject for this exploratory case study is a small Estonian media company having a total of 43 members/employees. Data for the study were collected using two questionnaires (organizational leadership capability and dimensions of learning organizations) and by in-depth interviews. Assessment and analysis of the data included: measurement of organizational leadership (OL) and learning organization; measurement of entrepreneurial behavior; and analysis of the results gained from studying the issues pertaining to OL, learning organization and entrepreneurial behavior. Findings: The results of this study reveal that part-time versus full-time employees have more positive attitudes toward the organization's decentralized leadership and of six of seven learning characteristics. It appears that the entrepreneurial orientation of the part-time employees (PTEs) helps explain the differences observed. Practical implications: The implications for practice based on this study is that firms should consider their PTEs as a valuable asset not only because of the flexibility they offer to the workforce but also because of the special skills and outlooks they bring to the organization. Originality/value: This paper explores the relationships among organizational learning, OL and entrepreneurship in context of part-time employment.